PROMOTING QUALITY OF LIFE AT WORK: EXPERIENCE REPORT OF A WORKSHOP INVOLVING NURSING STAFF - Anna Cláudia Maurício Telles; Patrícia Campos Pavan Baptista; Lucinda Helena da Silva de Vasconcelos; Carolina Luiza Bernardes; Ana Paula Pelegrini Ratier (Universidade Federal do Paraná, 2015)
The aim of the report is to describe the experience of a workshop focused on the Promotion of Quality of Life at Work with nursing staff. This is an experience report about the performance of a workshop with nursing staff of a university hospital. Participants in the workshop were 60 nursing staff, with six workstations for the Promotion of Quality of Life at Work. Six workstations were carried out, simultaneously, with approximately 10 workers in each and an average duration of 30 minutes. The stations were conducted by nurses and physiotherapists with the support of a professor, covering themes relevant to the Health of the worker. The report aims to contribute to broadening the discussions on the subject, offering subsidies to rethink the work process and possible interventions aimed at improving working conditions, empowering workers in relation to self-care and preventing accidents and diseases.